Picosecond to nanosecond dynamics provide a source of conformational entropy for protein folding. Issue 31 (18th July 2016) - Stadler, Andreas M.; Demmel, Franz; Ollivier, Jacques; Seydel, Tilo
Abstract : Myoglobin can be trapped in fully folded structures, partially folded molten globules, and unfolded states under stable equilibrium conditions. Abstract : Myoglobin can be trapped in fully folded structures, partially folded molten globules, and unfolded states under stable equilibrium conditions. Here, we report an experimental study on the conformational dynamics of different folded conformational states of apo- and holomyoglobin in solution. Global protein diffusion and internal molecular motions were probed by neutron time-of-flight and neutron backscattering spectroscopy on the picosecond and nanosecond time scales. Global protein diffusion was found to depend on the α-helical content of the protein suggesting that charges on the macromolecule increase the short-time diffusion of protein. With regard to the molten globules, a gel-like phase due to protein entanglement and interactions with neighbouring macromolecules was visible due to a reduction of the global diffusion coefficients on the nanosecond time scale. Diffusion coefficients, residence and relaxation times of internal protein dynamics and root mean square displacements of localised internal motions were determined for the investigated structural states. The difference in conformational entropy Δ S conf of the protein between the unfolded and the partially or fully folded conformations was extracted from the measured root mean square displacements. Using thermodynamic parameters from the literature and the experimentally determined Δ S conf values we could identify the entropic contribution of the hydration shell Δ S hydr of the different folded states. Our results point out the relevance of conformational entropy of the protein and the hydration shell for stability and folding of myoglobin.